Deskripsi Kemampuan Menyelesaikan Operasi Hitung Bilangan Penjumlahan Teknik Menyimpan pada Siswa Kelas 4 SDN 34 Parit Madura - Hanafi, Hanafi; Fatmawati, Risdiana Andika; Suriyana, Suriyana (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the ability of grade IV students of SDN 34 Parit Madura Sungai Ambawang in completing the operation of counting the number of addition of the storing technique. This type of research uses a qualitative approach. The data collection technique in this study uses test questions. The researcher gave test questions to students in grade IV IV SDN 34 Parit Madura Sungai Ambawang in analyzing the ability of students to complete the number counting operation of the addition of the storing technique. Data analysis uses qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results of the study showed that students' ability to calculate long stacked summing numbers was still very low. There were 2 out of 14 students who could answer the thesis questions well. Therefore, it can be concluded that students' ability to calculate long stacked summation numbers is still very low